THE ROLE OF PARENTS TOWARDS YOUTUBE USERS IN BUILDING CHILDREN'S RELIGIOUS BEHAVIOR IN KUALA PANGKALAN KERAMAT VILLAGE - Sarmila, Uray; Aslan, Aslan; Astaman, Astaman (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
The research results show that; Firstly, children prefer playing on the internet on YouTube compared to playing outside with their friends, because parents provide mobile phone facilities and freedom to children from a young age, so that parents can easily do their work without being disturbed, children are addicted to playing on mobile phones (playing YouTube ), and content on YouTube that attracts children's attention. Second, the role of complete parents and the role of single parents in providing religious education to children. There is not much difference between the role of a complete parent and the role of a single parent because in this study the researchers found that the role given by parents to children is to provide an example of good behavior, provide an example of worship, force children to worship so that they get used to it even though they are forced to do so. . There were not many differences that researchers found in this study, because basically parents have the same role between complete parents and single parents in providing education to their children